2012
DOI: 10.1590/s1808-18512012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Estudo clínico epidemiológico das fraturas da coluna vertebral

Abstract: OBJETIVO: Realizar um levantamento epidemiológico das fraturas da coluna vertebral. MÉTODOS: Estudo de revisão de prontuário, retrospectivo analisando dados clínicos e epidemiológicos no período de 1991 a 2010. Foram avaliados dados como: idade, sexo, procedência, escala de Frankel admissional, mecanismo de trauma, tipo de fratura, tratamento e complicações, nos prontuários de 1.917 pacientes submetidos a tratamento de fraturas da coluna vertebral. O teste do qui-quadrado foi utilizado para comparação entre as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
3
9
0
3
Order By: Relevance
“…A similar profile was noted by Vasconcelos and Riberto 20 and Morais et al 21 in other Brazilian studies, while Fernandes et al, 22 Frison et al 23 and lee et al 19 reported falls as the primary cause. Studies also vary with regards to the type of vehicle the victim was using at the time of the accident, [20][21][22] possibly as a result of environmental variations and/or variations in the local fleet of vehicles. In the study conducted, we noted that 54.1% of MVAs involved motorcycles, probably corroborated by the high number of this type of vehicle on the roads, the most common vehicle in the state of Tocantins, corresponding to 35.62% (158,024) of the total fleet in February 2012.…”
Section: Resultssupporting
confidence: 84%
“…A similar profile was noted by Vasconcelos and Riberto 20 and Morais et al 21 in other Brazilian studies, while Fernandes et al, 22 Frison et al 23 and lee et al 19 reported falls as the primary cause. Studies also vary with regards to the type of vehicle the victim was using at the time of the accident, [20][21][22] possibly as a result of environmental variations and/or variations in the local fleet of vehicles. In the study conducted, we noted that 54.1% of MVAs involved motorcycles, probably corroborated by the high number of this type of vehicle on the roads, the most common vehicle in the state of Tocantins, corresponding to 35.62% (158,024) of the total fleet in February 2012.…”
Section: Resultssupporting
confidence: 84%
“…Thus, we point out that as thoracic and cervical segments appear as the most committed, they refer to the greater risk of paraplegia and tetraplegia, respectively. Other studies corroborate with this [25,5] aspect, as well as the definitions of American Spine Injury Association for the neurological classification of TRM [3].…”
Section: Discussionsupporting
confidence: 74%
“…When the etiology of the trauma was diving in shallow water, this study has found its correspondence with the lesions in the cervical region, and these findings were shared by other researchers [25]. The authors also suggest changes in public policies, especially in urban areas, with education and prevention for falls from height campaigns, caution diving in shallow water and automobile and motorcycle accidents, in order to reduce cases of TRM.…”
Section: Discussionsupporting
confidence: 71%
“…1,6,8,[12][13][14][15] The most common fracture mechanisms were falls (46.87%) and traffic accidents (46.87%), as different from the world literature where falls prevail. 8,12,13 In our series, males predominated all causes, with a male to female ratio of 6.57:1, with a more balanced relationship if we consider car accidents alone, where the ratio was 1.5:1. The increase in cases of vertebral trauma in women can be attributed to their greater inclusion in the labor market and the consequent exposure to the risk of accidents.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the literature reports neurological deficit associated with thoracolumbar spine fractures in around 15-20% of the cases. 3,8,16 This difference may be attributed to the inclusion criteria in this study, since only patients with vertebral instability and an indication for surgery with more serious injuries and greater potential for causing spinal cord lesions were included.…”
Section: Discussionmentioning
confidence: 99%